2009
DOI: 10.1159/000232600
|View full text |Cite
|
Sign up to set email alerts
|

Higher Survival Rates of Chronic Hemodialysis Patients on Anti-Hypertensive Drugs

Abstract: Background: The effects of anti-hypertensive drugs on survival have not been examined in a large cohort of hemodialysis (HD) patients. Methods: We examined the relationship between blood pressure, anti-hypertensive drug therapy, and survival using the nationwide HD registry of the Japanese Society for Dialysis Therapy. Outcomes were confirmed using the coded ID numbers of the 2005 and 2006 registries. Logistic analyses were performed to determine the effect of anti-hypertensive drug therapy on survival. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 66 publications
1
20
1
2
Order By: Relevance
“…Iseki et al examined the relationship between BP and anti-hypertensive drugs therapy in HD patients, and found that one-year mortality rate was significantly lower in patients prescribed anti-hypertensive drugs than in those non-prescribed. They refer to effect of the prescription of anti-hypertensive drugs on good prognosis of HD patients [19]. In fact, the percentage of the patients prescribed anti-hypertensive drugs was higher in non-CCVD patients than in CCVD patients in this study (66% vs. 33%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Iseki et al examined the relationship between BP and anti-hypertensive drugs therapy in HD patients, and found that one-year mortality rate was significantly lower in patients prescribed anti-hypertensive drugs than in those non-prescribed. They refer to effect of the prescription of anti-hypertensive drugs on good prognosis of HD patients [19]. In fact, the percentage of the patients prescribed anti-hypertensive drugs was higher in non-CCVD patients than in CCVD patients in this study (66% vs. 33%).…”
Section: Discussionmentioning
confidence: 56%
“…Finally, some race-related factors might be associated with the long survival and low incidence of CCVDs because all of our study patients were Japanese. In fact, rates of mortality and comorbid diseases differ among countries [19,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Although several randomized control trials (RCTs) showed that RASI reduced the incidence of deaths, patient numbers were small and the studies used an open-label design [9-12]. Similar results were obtained from observational studies, but these did not estimate the effect of ACEI and ARB separately [13-15] and did not consider the possibility of time-dependent confounding: blood pressure (BP) levels probably associated with mortality [16] are both affected by previous RASI use and influence the future prescription of RASI. This time-dependent confounding cannot be adjusted appropriately and produces bias if conventional analysis such as time-dependent Cox regression is used [17, 18].…”
Section: Introductionmentioning
confidence: 89%
“…Almost all patients have past history of hypertension before starting dialysis and have taken multiple anti-hypertensive medications. It has been reported by several cohort studies including JSDT registry [26] and metaanalyses [27,28] that BP control by anti-hypertensive drugs leads to better cardiovascular outcomes. However, any optimal regimen to control BP and to reduce mortality has not yet been established.…”
Section: Treatment By Anti-hypertensive Drugs For Hd Patientsmentioning
confidence: 99%